Studi Morfologi Stomata Daun Glodokan (Polyalthia longifolia Sonn) pada Lingkungan Berbeda - Munir, Asmawati; Darlian, Lili; Nurjaya, Sri (bionature, 2019)
Abstract. This study investigated a natural acid-base indicator which is extracted from plants in Kupang city. There are 14 plants that potential as a source of natural indicator for acid base titration, i.e, KolUngu (Brassica oleracea Capitata Group), Turi Merah flower (Sesbania grandiflora L. Pers), BelimbingWuluh flower (Averhoa bilimbi L), Kaktus Merah fruit (Opuntia vulgaris Mill), Ruelia flower (Ruellia simplex), Flamboyan flower (Delonix regia), bugenvil flower (Bougainvillea spectabilisWilld.), Bayam Merah leaves (Amaranthus tricolor L.) Jamblang fruit (Syzygiumcumini L.), Murbey fruit (Morus alba L.), Pinang fruit (Areca catechu L.), Sirih fruit (Piper betle L.), Kunyit (Curcuma longa Linn), and Nanas Kerang leaves (Rhoeo discolor). Plants extract shows a sharp color change in acid and base solution. Promising results as a natural indicator also shown in acid base titration which is have similar equivalent point to synthetic indicator. We can use these natural indicators as an alternative to synthetic indicator because they are found to be simple, very useful, cheap, easy to extract, accurate, and eco-friendly. Keywords: plant, natural indicator, acidbase.